Approach to the ethical principles of Latin American liberation subject in the thought of Enrique Dussel - Enrique Leones Ortega (Amauta, 2018)
With this dissertation we intend to reflect on the ethical principles that underlie the practice of liberation of Latin American subject in the context of philosophical thought of Enrique Dussel. To this end, they consider, first, biographical aspects of the author in question and the importance of his work, as well as the origins and development of ethical thought in the philosophical tradition that serves as a generational context. Then, relations between the foundations and principles of ethics of liberation with the tradition of ethical materials, and their challenges to other traditions of ethical thought are determined also that it is specified in the criteria provided by the dusseliana liberation ethics, such as: the complex philosophical categorical system, the ana lectical method of thinking and a mapping of the problems of contemporary ethical reality. Finally, some considerations about the Latin American subject in the context of the global situation paradoxical globalization/exclusion of the vast majority of humanity arise.